Limited impact of climate forcing products on future glacier evolution in Scandinavia and Iceland - Compagno, Loris; Zekollari, Harry; id_orcid:0 000-0002-7443-4034; Huss, Matthias; id_orcid:0 000-0002-2377-6923; Farinotti, Daniel; id_orcid:0 000-0003-3417-4570 (Cambridge University Press, 2021)
Due to climate change, worldwide glaciers are rapidly declining. The trend will continue into the future, with consequences for sea level, water availability and tourism. Here, we assess the future evolution of all glaciers in Scandinavia and Iceland until 2100 using the coupled surface mass-balance ice-flow model GloGEMflow. The model is initialised with three distinct past climate data products (E-OBS, ERA-I, ERA-5), while future climate is prescribed by both global and regional climate models (GCMs and RCMs), in order to analyze their impact on glacier evolution. By 2100, we project Scandinavian glaciers to lose between 67 ± 18% and 90 ± 7% of their present-day (2018) volume under a low (RCP2.6) and a high (RCP8.5) emission scenario, respectively. Over the same period, losses for Icelandic glaciers are projected to be between 43 ± 11% (RCP2.6) and 85 ± 7% (RCP8.5). The projected evolution is only little impacted by both the choice of climate data products used in the past and the spatial resolution of the future climate projections, with differences in the ice volume remaining by 2100 of 7 and 5%, respectively. This small sensitivity is attributed to our model calibration strategy that relies on observed glacier-specific mass balances and thus compensates for differences between climate forcing products. ISSN:0022-1430 ISSN:1727-5652